THE STUDY OF ONLINE SHOPPING CONTINUANCE INTENTION OF SHOPEE CUSTOMERS IN MANADO - Wowor, Wenseslaus; Pangemanan, Sifrid S.; Wangke, Shinta J. C. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: A rapidly growing human civilization is also followed by a rapid development of information technology. The current rapid technological development is caused by the presence of internet.This study aims to gain understanding of the customer online shopping continuance intention at Shopee platform in Manado. This research is a qualitative research and uses descriptive type of research where it will investigate the customer online shopping continuance intention at Shopee platform in Manado. This research concludes that the process of continuance intention of using Shopee platform in Manado is occurred through several steps, namely expectation of the platform, perception of the performance, user satisfaction, and continuance intention to use the platform again. Users of Shopee platforms in Manado felt that their expectation of software have been met, and after the usage of the platform, the users are satisfied with the usefulness and easiness of use of the platform, thus create loyalty and intention to use Shopee continuously. Recommendation shopee should strive to keep on updating and improving its platform consistently, in order to provide better experience and thus greater customer loyalty.Â Keywords: perceived usefulness, perceived ease of use, continuance intention